Effectiveness of Holter Monitoring in the Detection of Atrial Fibrillation after Ischemic Stroke: Holter Monitoring in the Detection of Atrial Fibrillation after Ischemic Stroke - Rahman, Hameed Ur; Hashmat, Asif; Mustafa, Mehwish; Rehman, Wali; Khan, Tariq; Tahir, Farhan (Pakistan Journal of Health Sciences, 2026)
Atrial fibrillation (AF) is an important but often hidden cause of recurrent ischemic stroke, requiring early detection for timely anticoagulation. This study assessed the effectiveness of 72-hour Holter monitoring in identifying previously undiagnosed AF in acute ischemic stroke patients, particularly in resource-limited settings. Objectives: To determine the effectiveness of 72-hour Holter monitoring in identifying previously undiagnosed AF in acute ischemic stroke patients. Methods: This analytical cross-sectional study was conducted at the Department of Neurology, Pak Emirates Military Hospital, Rawalpindi, from May to September 2025, enrolling 256 patients with neuroimaging-confirmed ischemic stroke. Holter monitoring was initiated within 2 hours of admission and continued for 72-hours, accompanied by 8-hourly pulse checks and symptom logs to identify AF episodes lasting ≥30 seconds. Chi-square or Fisher’s exact tests were used, keeping p≤0.05 statistically significant. Results: The mean age was 65.4±11.2 years; 59.4% were male. AF was detected in 17 patients (6.6%), with 72-hour Holter yielding significantly higher detection than baseline ECG (17(6.6%) vs.5(2.0%), p=0.002, with diagnostic accuracy of 95.3%. Cumulative detection increased over time: 29.4% within 24 hours, 70.6% by 48 hours, and 100% by 72 hours. AF was significantly associated with age ≥65 years (p=0.008), hypertension (p=0.047), and diabetes (p=0.029). Conclusions: 72-hour Holter monitoring is a useful non-invasive method of correctly detecting occult AF in patients after acute ischemic stroke, with superior diagnostic yield over baseline ECG. These results favor routine use of 72-hour Holter monitoring as part of post-stroke protocols.